Regenerative Medicine - Steinhoff, Gustav; SpringerLink (Online service). (Dordrecht New York Springer, 2011)
Regenerative Medicine is a fastly emerging interdisciplinary field of research and clinical therapies on the repair, replacement or regeneration of cells, tissues or organs in congenital or acquired disease. This new field of research and clinical development focussing on stem cell science and regenerative biology is just starting to be the most fascinating and controversial medical development at the dawn of the 21st century. Viewing the great expectations to restructure and regenerate tissue, organs or organisms the current attempts of scientist and physicians are still in an early phase of development. This new textbook on ?Regenerative Medicine ? from protocol to patient? is aiming to explain the scientific knowledge and emerging technology as well as the clinical application in different organ systems and diseases. The international leading experts from four continents describe the latest scientific and clinical knowledge of the field of ?Regenerative Medicine?. The process of translating science of laboratory protocols into therapies is explained in sections on basic science, clinical translation, regulatory, ethical and industrial issues. The textbook is aiming to give the student, the researcher, the health care professional, the physician, and the patient a complete survey on the current scientific basis, therapeutical protocols, clinical translation and practised therapies in Regenerative Medicine.
1 History of Regenerative Medicine, Raymund E. Horch, Laurentiu M. Popescu, and Elias Polykandriotis -- Part I Biology of tissue regeneration: 2 Extracellular Matrix and Tissue Regeneration, Yrjö T. Konttinen et al -- 3 Stem Cell Niche, Pei Wen, Pei Sun and Rongwen Xi -- 4 Stem Cells and Asymmetric Cell Division, Frank Hirth -- 5 Stem Cells in the Developing and Adult Nervous System, Fumitaka Osakada and Masayo Takahashi -- Part II Stem cell science and technology: 6 Characterization and Classifi cation of Stem Cells, Andreas Bosio, Ute Bissels and Stefan Miltenyi -- 7 Human Embryonic Stem Cells, Mikael C.O. Englund, Peter Sartipy, Johan Hyllner -- 8 Induced Pluripotent Stem Cells, Kazutoshi Takahashi and Shinya Yamanaka -- 9 Generation of Germline-Derived Stem Cells from the Adult Human Testis, Thomas Skutella and Sabine Conrad -- 10 Hematopoietic Stem Cells, Jonathan Frampton -- 11 Cardiovascular Stem Cells, Christoph Brenner, Robert David and Wolfgang-Michael Franz -- 12 Cardiac Stem Cells: Tales, Mysteries and Promises in Heart Generation and Regeneration, Maurizio Pesce, Giulio Pompilio , Elisa Gambini, Maurizio C. Capogrossi -- 13 Neural Stem Cells, Yoko Arai, Wieland B. Huttner and Federico Calegari -- 14 Liver Stem Cells, Tohru Itoh, Minoru Tanaka, and Atsushi Miyajima -- 15 Cancer Stem Cells, Murali MS Balla, Anjali P. Kusumbe, Geeta K. Vemuganti and Sharmila A. Bapat -- 16 Mesenchymal Stem Cells: An Oversimplifi ed Nomenclature for Extremely Heterogeneous Progenitors, Patrick Wuchter, Wolfgang Wagner, Anthony D. Ho -- 17 Musculoskeletal Stem Cells, Gerben M. van Buul and Gerjo J.V.M. van Osch -- Part III Tissue Engineering, Biomaterials and Nanotechnology: 18 Vector Technology and Cell Targeting: Peptide-Tagged Adenoviral Vectors as a Powerful Tool for Cell Specifi c Targeting, B.M. Pützer and A. Schmidt -- 19 Regenerative Chimerism Bioengineered Through Stem Cell Reprogramming, Timothy J. Nelson, Almudena Martinez-Fernandez and Satsuki Yamada -- 20 Biodegradable Materials, Michael Schroeter, Britt Wildemann, Andreas Lendlein,  Andre Terzic -- 21 Functionalized Nanomaterials, Jie Zhou, Wenzhong Li, Changyou Gao -- 22 Biointerface technology, Joachim Rychly -- Part IV Regenerative Therapies: 23 Blood, Michael Schmitt and Mathias Freund -- 24 Regenerative Medicine in the Central Nervous System: Stem Cell-Based Gene-Therapy, Seung U. Kim -- 25 Regenerative Therapy for Central Nervous System Trauma, K.K. Jain -- 26 Regenerative Therapies for the Ocular Surface, Geeta K. Vemuganti, Virender S. Sangwan, Indumathi Marriappan and Dorairajan Balasubramanian -- 27 The Development of a Stem Cell Therapy for Deafness, Nopporn Jongkamonwiwat  and Marcelo N. Rivolta -- 28 Dental, Kristina Arvidson, Sølve Hellem and Kamal Mustafa -- 29 Trachea, Silvia Baiguera and Paolo Macchiarini -- 30 Lung, Lavinia Coltan and Bernard Thébaud -- 31 Vascular Regeneration: Endothelial Progenitor Cell Therapy for Ischemic Diseases, Atsuhiko Kawamoto, Masaaki Ii and Takayuki Asahara -- 32 Heart, Gustav Steinhoff and Bodo Eckehard Strauer -- 33 Liver, Amar Deep Sharma, Razvan Iacob, Michael Bock, Tobias Cantz, Michael P. Manns and Michael Ott -- 34 Kidney, Hermann Haller and Sajoscha A. Sorrentino -- 35 Skin, Hans-Günther Machens, Christina Irene Günter, and Augustinus Bader -- 36 Preclinical Animal Models for Segmental Bone Defect Research and Tissue Engineering, Johannes C. Reichert, A. Berner, Siamak Saifzadeh, Dietmar W. Hutmacher -- 37 Constraints to Articular Cartilage Regeneration, Georg N. Duda, Joshua O. Eniwumide, and Michael Sittinger -- 38 Muscle and Ligament Regeneration, Thomas Mittlmeier and Ioannis Stratos -- Part V Regulation and Ethics: 39 Regulatory Frameworks for Cell and Tissue Based Therapies in Europe and the USA, Gudrun Tiedemann and Sebastian Sethe -- 40 Ethics and Law in Regenerative Medicine: A Legal and Ethical Outline on Regenerative Medicine in Research in France, Germany and Poland, Gregor Becker and Anna Grabinski -- 41 Patient Propositions: $9.6 Billion of Medical Research Funding, Robert N. Klein II -- Index.
Electronic reproduction.
Keywords: Regenerative medicine; Stem cell -- Therapeutic use; Electronic books